Assessing the effectiveness of drywells as tools for stormwater management and aquifer recharge and their groundwater contamination potential - Edwards, Emily C.; Harter, Thomas; Fogg, Graham E.; Washburn, Barbara; Hamad, Hamad (Journal of hydrology (Amsterdam), 2016)
•Drywells are vadose zone infiltration wells that can be used to recharge groundwater.•Thirteen field studies are examined that have explored drywell environmental effects.•Studies show that when managed correctly drywells do not pose risk to groundwater.•Studies show that drywell use can aid aquifer recharge.•Studies show that site hydrogeologic system plays key role in contaminant attenuation. Drywells are gravity-fed, excavated pits with perforated casings used to facilitate stormwater infiltration and groundwater recharge in areas where drainage and diversion of storm flows is problematic. Historically, drywells have predominantly been used as a form of stormwater management in locations that receive high volumes of precipitation; however the use of drywells is increasingly being evaluated as a method to supplement groundwater recharge, especially in areas facing severe drought. Studies have shown that drywells can be an effective means to increase recharge to aquifers; however, the potential for groundwater contamination caused by polluted stormwater runoff bypassing transport through surface soil and near surface sediment has prevented more widespread use of drywells as a recharge mechanism. Numerous studies have shown that groundwater and drinking water contamination from drywells can be avoided if drywells are used in appropriate locations and properly maintained. The effectiveness of drywells for aquifer recharge depends on the hydrogeologic setting and land use surrounding a site, as well as influent stormwater quantity and quality. These parameters may be informed for a specific drywell site through geologic and hydrologic characterization and adequate monitoring of stormwater and groundwater quality.